Mobile marketing how mobile technology is revolutionizing marketing, communications, and advertising - Rowles, Daniel (Kogan Page, 2014)
" A growing portion of internet traffic is coming from smartphones and tablets. Net Marketshare put mobile's share of global browsing traffic at 10.3% in October 2012. This was the first time mobile had topped 10% of all browsing. In North America, the share of Web traffic from smart phones and tablets was estimated at 28% as of June 2012, with the time spent with mobile growing at 14 times the rate of desktop media. Although the importance of mobile technologies for marketing communications is widely recognized, the use of proper strategy is not really understood by a lot of marketers. To help determine what marketers can do and should be doing with the exponential growth in mobile device ownership, Daniel Rowles gives practical and hands-on training on how to design, implement and measure an effective digital strategy. Combining theoretical understanding of mobile's role in the marketing arena and practical exercises, Rowles teaches how to build a top-down strategy, encompassing all consumer touch points, to future-proof businesses against customers' ever-changing mobile interaction with brands"